What influences the location choice of establishments? An analysis considering establishment types and activities interactions - Riahi Samani, Ali; Mishra, Sabyasachee; Golias, Mihalis; Lee, David J.H. (My University, 2023)
Over the years, research on firm location choice has received less attention than residential location choices. Although valuable efforts have been made to model firms' location choices, investigations on the location choice of smaller economic units (establishments) and differences between location determinants of various activities can provide better insights into the interaction between land use and transportation network. This study aims to, first, model the location choice of establishments considering the North American Industrial Classification System (NAICS) sectors and examine the impact of spatial components; second, evaluate how the location determinants of establishments vary across industry sectors; third, assess the interdependence between different establishments' location choices; and fourth, estimate and compare the Willingness to Pay of different activities for better accessibility. A discrete choice model is incorporated to model establishments' location preferences, where first, based on the selected parcel by each establishment, a set of competitive alternatives are generated, creating a constrained choice set, and then, the actual choice of an alternative is estimated using a multinomial logit model. The developed model is implemented on the data collected from the state of Tennessee, USA. Results suggested that spatial location determinants can be categorized into four categories: accessibility, neighborhood characteristics, office profile, and presence of other activities. Moreover, agglomeration, land value, office size, square feet, and surrounding land use conditions are the most important location determinants. The finding of this study provides valuable information to transportation planners on interactions between establishments' locations, demographic conditions, and transportation networks.
Keywords: Establishment location choice; Location determinants; Discrete choice model; Establishment types; Willingness to pay